2020
DOI: 10.1152/ajpcell.00305.2020
|View full text |Cite
|
Sign up to set email alerts
|

Out of breath, out of time: interactions between HIF and circadian rhythms

Abstract: Humans have internal circadian clocks that ensure important physiological functions occur at specific times of the day. These molecular clocks are regulated at the genomic level and exist in most cells of the body. Multiple circadian resetting cues have been identified, including light, temperature and food. Recently, oxygen has been identified as a resetting cue and emerging science indicates that this occurs through interactions at the cellular level between the circadian transcription-translation feedback l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…The cellular response to low oxygen is regulated by hypoxia-inducible factors (HIFs), members of the basic helix-loop-helix-PAS family of transcription factors that includes BMAL1. HIF and BMAL1 share homologies in their dimerization domains and DNA-binding motifs, enabling cross-talk between the circadian and hypoxia signaling pathways (O’Connell et al, 2020; Peek, 2020). Tissue oxygenation and oxygen consumption show daily rhythms in mice (Adamovich et al, 2017; Adamovich et al, 2019), and in vitro studies show that cellular clocks are synchronized in an HIF-dependent manner (Adamovich et al, 2019).…”
Section: Host Immune Responses and Covid-19 Pathologymentioning
confidence: 99%
“…The cellular response to low oxygen is regulated by hypoxia-inducible factors (HIFs), members of the basic helix-loop-helix-PAS family of transcription factors that includes BMAL1. HIF and BMAL1 share homologies in their dimerization domains and DNA-binding motifs, enabling cross-talk between the circadian and hypoxia signaling pathways (O’Connell et al, 2020; Peek, 2020). Tissue oxygenation and oxygen consumption show daily rhythms in mice (Adamovich et al, 2017; Adamovich et al, 2019), and in vitro studies show that cellular clocks are synchronized in an HIF-dependent manner (Adamovich et al, 2019).…”
Section: Host Immune Responses and Covid-19 Pathologymentioning
confidence: 99%
“…Taken together, prime circadian oscillatory mechanisms are intertwined with hypoxia inducible factors. These interactions could potentially alter the function of the circadian system under hypoxic conditions [15]. This hypothesis was supported by recent -omics studies in rodents.…”
Section: Molecular Rhythms In Osamentioning
confidence: 68%
“…Additionally, sleep fragmentation can be a potential hallmark for this health condition [11]. Recent studies have shown that exposure to hypoxic conditions can alter circadian gene expression and associated biological processes [12][13][14][15]. More importantly, chronic exposure to hypoxic conditions can lead to disorders that are commonly associated with the dysregulation of circadian rhythms including cardiovascular diseases, respiratory diseases, dementia, cancer, and metabolic disorders [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, as recently reviewed in the American Journal of Cell Physiology, the connection between hypoxia-response through HIF and circadian rhythm goes beyond the equally important evolutionary pressures of oxygen handling and light/day cycle; HIF can interact directly with the target of the circadian gene promoter known as E-box, directly affecting cellular rhythmicity (133). It is tempting, therefore, to hypothesize a link between this circadian dysregulation and the tissue-specific HIF contribution to PH development (224).…”
Section: Brain and Muscle Arnt-like 1 (Bmal1)mentioning
confidence: 99%